If it's not what You are looking for type in the equation solver your own equation and let us solve it.
63-4y=10
We move all terms to the left:
63-4y-(10)=0
We add all the numbers together, and all the variables
-4y+53=0
We move all terms containing y to the left, all other terms to the right
-4y=-53
y=-53/-4
y=13+1/4
| -2x+7-2x=-37 | | -3f-8=-4f | | 8f+7=-9 | | 2(x+11)+7x=9x-22 | | -2u-6+4u=10-2u | | -3-4(t-4)=-7 | | 5m-10=10 | | -10+6j=10+4j | | x+3/8=91/8 | | -3(y+4)+6y=24 | | -9u-8=-10u | | 8-3b=-9b-10 | | 5m=4m-6 | | 6(r-4)=24 | | 6(r–4)=24 | | -10-2y=-4y | | -30=-9x=-3 | | -r-9=-2r | | q=-8q-9 | | 5/37x+15/37=15/37 | | 1.4-3.7x=-4.2x+0.3 | | 5v=24+v | | x/6-9=-14 | | 72+2w=10w | | 5x-8x-14=1 | | 3x-6=4x+14 | | 20=2x= | | 8c=4c+4c | | 7(x–3)=7 | | 2(x2)+10=60 | | 0.25y+9.99=113.774 | | 6,513+x=7,378 |